If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x)=x2+2x+26
We move all terms to the left:
(x)-(x2+2x+26)=0
We add all the numbers together, and all the variables
-(+x^2+2x+26)+x=0
We get rid of parentheses
-x^2-2x+x-26=0
We add all the numbers together, and all the variables
-1x^2-1x-26=0
a = -1; b = -1; c = -26;
Δ = b2-4ac
Δ = -12-4·(-1)·(-26)
Δ = -103
Delta is less than zero, so there is no solution for the equation
| 77=-8b+5 | | (7x+6)=(7x+6) | | 12u=8u+32 | | s-8=-15 | | 7w+35=75 | | 34=2r+8(1+3r) | | .75c+7c=2.80 | | x-3*2=x-2*3 | | 8=4=2q | | .75+7c=2.80 | | (3x+15)=(4x) | | 42=2(2w+3)+2w | | 1=3p-5 | | 4x-92=180 | | 5-2m=3+m | | 3x+10+2x=70 | | 6(2x+2)=2(6x+6) | | -100=-2+7v | | 4u=18 | | (x+1)=(7x-5 | | 5x-28=x-36 | | 60=7x+x+4 | | 4z2–19z+12=0 | | 5(2x+12)=30+10x+30 | | 7-+10a=9-9a | | 4x+3x+9=4x–3x+9 | | 11-104=8x | | 2x+14=39 | | d^2=14d | | 9c+24=10 | | -7r-9=33 | | d^2=14 |